2017
DOI: 10.1111/ene.13484
|View full text |Cite
|
Sign up to set email alerts
|

Cortical superficial siderosis and acute convexity subarachnoid hemorrhage in cerebral amyloid angiopathy

Abstract: Amongst patients with CAA, cSS is independently associated with acute cSAH. These findings suggest that cSAH may be involved in the pathogenesis of the cSS observed in CAA. Longitudinal studies are warranted to assess this potential causal relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Two cohort studies showed that the majority of patients with CAA-related TFNEs (first ever or recurrent) have one or both of cSAH or cSS (58% 5 and 83% 13 , respectively). Disseminated cSS is much more common in CAA patients presenting with TFNEs than CAA patients presenting with ICH 15,16 .…”
Section: Neuroimagingmentioning
confidence: 99%
“…Two cohort studies showed that the majority of patients with CAA-related TFNEs (first ever or recurrent) have one or both of cSAH or cSS (58% 5 and 83% 13 , respectively). Disseminated cSS is much more common in CAA patients presenting with TFNEs than CAA patients presenting with ICH 15,16 .…”
Section: Neuroimagingmentioning
confidence: 99%
“…We investigated the clinical and imaging factors associated with mixed CMB compared to strictly lobar CMB (suggesting CAA) and strictly deep CMB (suggesting HA). We also evaluated whether CMB distribution in patients with mixed CMB may indicate underlying SVD by testing the associations of the ratio lobar / total CMB count with symptomatic lobar ICH and cortical superficial siderosis (cSS), key neuroimaging markers of CAA (7, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…The presented case was CAA-related ICH accompanied by massive SAH, although the volume of parenchymal haematoma was relatively small (Patel et al, 2009 ). Severe SAH resembling that of aneurysmal origin is rare in CAA (Ohshima et al, 1990 ; Charidimou et al, 2015 ; Ni et al, 2015 ; Raposo et al, 2018 ). Old age and pancreatic cancer may have exacerbated the bleeding from the Aβ-positive vessels into the subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding into the subarachnoid space is also common in CAA, presenting as convexity subarachnoid haemorrhage (SAH) in acute and superficial siderosis in the chronic phase. However, CAA is seldom described as a cause of massive SAH resembling aneurysmal rupture (Ohshima et al, 1990 ; Charidimou et al, 2015 ; Ni et al, 2015 ; Raposo et al, 2018 ). Here, we report an autopsied case of widespread SAH related to CAA.…”
Section: Introductionmentioning
confidence: 99%